2009
DOI: 10.1007/s00534-009-0204-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hilar cholangiocarcinoma in the new era: the Asan experience

Abstract: Background/purpose Both curative resection and minimized in-hospital mortality offer the only chance of longterm survival in patients with hilar cholangiocarcinoma. The reported resectability rates for hilar cholangiocarcinoma have increased by virtue of combined major hepatectomy, but this procedure is technically demanding and still associated with a significant morbidity and mortality that must be carefully balanced against the chances of longterm survival. Methods Between January 2001 and December 2008, 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
195
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(215 citation statements)
references
References 25 publications
13
195
3
2
Order By: Relevance
“…Several reports also showed that PVE enables surgical resection in cases that are initially considered as unresectable due to the shortage of future remnant liver volume [123]. However, the indication of PVE differs by institutions and no consensus exists [72,[123][124][125][126][127][128][129][130][131][132][133].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports also showed that PVE enables surgical resection in cases that are initially considered as unresectable due to the shortage of future remnant liver volume [123]. However, the indication of PVE differs by institutions and no consensus exists [72,[123][124][125][126][127][128][129][130][131][132][133].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…In many studies, the prognosis of patients who received combined PVR is poorer than that of patients who undergo surgical resection without PVR. However, the majority of these studies also show the prognosis of patients treated with combined PVR is significantly longer than the prognosis of unresected patients, especially in patients with hilar/upper bile duct carcinoma [71,72,74,116,155,156]. According to these reports, PVR is a safe procedure and may contribute to longer survival for patients with biliary tract cancers invading portal vein, although there is no prospective study for estimating the benefit of PVR.…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…A negative resection margins surgery represents the most important determinant of survival in patients with PHC (5)(6)(7)(8). The curative-intent surgery for PHC has significantly changed over the years from simple bile duct resection (1,9,10) to more complex surgical procedures (5,8,11).…”
Section: Introductionmentioning
confidence: 99%
“…The curative-intent surgery for PHC has significantly changed over the years from simple bile duct resection (1,9,10) to more complex surgical procedures (5,8,11). Thus, nowadays, a curative-intent surgery for PHC includes bile duct resection, loco-regional lymph nodes dissection, caudate lobectomy and, usually, a major hepatectomy (3,5,8,11,12). These complex surgical procedures were associated with significantly improved long-term survival rates compared with simple bile duct resection (13), however, at the expense of increased morbidity rates and relatively high mortality rates (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation